Implementation of General Election Commission Regulation Number 19 Of 2019 In Continuous 2020 Elections In Sigi Regency - Rosnawati Rosnawati; Slamet Riadi; Asrifai Asrifai (LPPM Universitas PGRI Sumatera Barat, 2025)
This study aims to determine the process of implementing the General Election Commission Regulation Number 19 of 2019 in the 2020 Simultaneous Elections in Sigi Regency. The method used in this study is qualitative with a descriptive approach. Qualitative research is a study where a researcher is placed as a key instrument in a study, data collection is carried out by combining and analyzing inductive data. The results of the study indicate that only the resource aspect is running well, this is due to the availability of qualified human resources, the availability of budget and the availability of supporting facilities and infrastructure in the process of implementing KPU Regulation Number 19 of 2019. However, in the communication aspect, the disposition and bureaucratic structure have not run according to expectations. In the communication aspect, it shows that the consistency dimension has not been fulfilled due to conflicting regulations between the Sigi Regency KPU and the Sigi Regency Population and Civil Registration Office regarding the requirements for voters. In terms of disposition, there is a visible commitment, but at the same time, its implementation is hampered by regulations related to population administration and errors in the DP4 data used as a basis for updating voter data. Meanwhile, in terms of bureaucratic structure, it has not run well due to differences in procedures or SOPs between the Sigi Regency KPU and the Sigi Regency Population and Civil Registration Office which are based on conflicting regulations that serve as the basis for them to carry out their duties, and is exacerbated by the DP4 from the Indonesian KPU which does not correspond to the facts on the ground. The reasons for the poor implementation of General Elections Commission Regulation Number 19 of 2019 were several issues, such as conflicting reference regulations between the Sigi Regency General Elections Commission (KPU) and the Sigi Regency Population and Civil Registration Office, the absence of a single standard operating procedure (SOP) that must serve as an absolute reference for data updating and the preparation of the final voter list (DPT), and the lack of public participation in ensuring the success of the 2020 simultaneous regional elections